Geriatric Assessment and Tools for Predicting Treatment Toxicity in Older Adults With Cancer. Issue 4 (July 2017) - Li, Daneng; Soto-Perez-de-Celis, Enrique; Hurria, Arti
Abstract : Abstract: Cancer is a disease of older adults, and the majority of new cancer cases and deaths occur in people 65 years or older. However, fewer data are available regarding the risks and benefits of cancer treatment in older adults, and commonly used assessments in oncology fail to adequately evaluate factors that affect treatment efficacy and outcomes in the older patients. The geriatric assessment is a multidisciplinary evaluation that provides detailed information about a patient's functional status, comorbidities, psychological state, social support, nutritional status, and cognitive function. Among older patients with cancer, geriatric assessment has been shown to identify patients at risk of poorer overall survival, and geriatric assessment-based tools are significantly more effective in predicting chemotherapy toxicity than other currently utilized measures. In this review, we summarize the components of the geriatric assessment and provide information about existing tools used to predict treatment toxicity in older patients with cancer.